Hubungan Pengetahuan Tentang Diabetes Dengan Perilaku Pemeriksaan Kadar Gula Darah Masyarakat Desa X, Kabupaten Ponorogo - An Nisa Aulia Kamila; Endang Dwi Yanti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Diabetes is one of the most prevalent non-communicable diseases worldwide and a major public health concern, including in Indonesia. Limited public knowledge about diabetes can reduce awareness of the importance of regular blood glucose monitoring as an early detection and complication prevention effort. This study aimed to determine the relationship between knowledge level about diabetes and blood glucose monitoring behavior among residents of X Village, Ponorogo Regency. Using a quantitative approach with a descriptive analytic design and cross-sectional method, 100 respondents were selected through proportional random sampling. Data were collected using a structured questionnaire assessing diabetes knowledge and blood glucose monitoring frequency. Bivariate analysis with the Chi-Square test, followed by Monte Carlo and Fisher’s Exact Test, was conducted due to cells with expected counts below five. The results showed a significant relationship between knowledge level and blood glucose monitoring behavior (p = 0.019; Fisher’s Exact Test). Respondents with higher knowledge were more likely to perform regular monitoring than those with poor or incorrect understanding. These findings highlight that knowledge plays a crucial role in shaping preventive health behaviors by enhancing risk awareness, motivation, and self-efficacy. Continuous health education is essential to strengthen early diabetes detection behaviors in rural communities.